Computer and computing technologies in agriculture IV : 4th IFIP TC 12 conference, CCTA 2010, Nanchang, China, October 22-25, 2010, selected papers - Chen, Yingyi; Li, Daoliang; Liu, Yande (IFIP advances in information and communication technology, 344-347, 2011)
Constitutes Part I of the refereed four-volume post-conference proceedings of the 4th IFIP TC 12 International Conference on Computer and Computing Technologies in Agriculture, CCTA 2010, held in Nanchang, China, in October 2010